Functionalization of CNTs surface with phosphonuim based deep eutectic solvents for arsenic removal from water - AlOmar, M.K.; AlSaadi, M.A.; Akib, S.; Hayyan, M.; Hashim, M.A. (Elsevier, 2016)
Herein, we present the use of deep eutectic solvent (DES) as functionalization agents for carbon nanotubes (CNTs) to form novel adsorbents for removal of arsenic ions (As3+) from water. Two DESs systems were prepared using methyltriphenylphosphonium bromide (MTPB) and benzyltriphenylphosphonium chloride (BTPC) as salts, in conjugation with glycerol (Gly) as a hydrogen bond donor. The resulting novel adsorbents were characterized using thermogravimetric analysis (TGA), Zeta potential, Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, XRD, EDX, FESEM, and BET surface area. Optimization studies were carried out utilizing RSM-CCD experimental design to estimate the optimum removal conditions for each adsorbent. The adsorption experimental data of both adsorbents were found to fit well with pseudo-second-order kinetics model, as well as with Langmuir and Freundlich adsorption isotherm models. The maximum adsorption capacity of a MTPB-DES-functionalized CNTs adsorbent was 23.4 mg/g.